Jungle green khaki brown Malaya's fight against terrorism - TV3; Grand Brilliance Sdn. Bhd. ([Kuala Lumpur] : TV3 : Nickleodean Books (M) Sdn. Bhd (edaran), 2007)
The documentary series depicts how our nations faced an era of terror for 12 years from 1948-1960, and the strategies adopted which culminated in victory
Seeds of insurgency (21 min.) -- Prelude to emergency (21 min.) -- Emergency declared (20 min.) -- The warriors of Bukit Kepong (20 min.) -- Government countermeasures (21 min.) -- The battle of Sungai Semut (21 min.) -- The turning point and road to merdeka (21 min.) -- The end of emergency (21 min.) --
Title from title screen
Keywords: Documentary films; Malaysia -- History